Revolutionizing Biomedical Education: Student Views on Virtual Reality in Anatomy and Physiology Learning - Poot, Erna Faryza Mohd; Arsyi, Reza Nur (International Journal of Educational Qualitative Quantitative Research, 2025)
In the era of digital transformation, biomedical education faces growing challenges to deliver more visual, interactive, and contextualized learning experiences. Virtual reality (VR) has emerged as a disruptive technology capable of revolutionizing how students deeply understand anatomy and physiology. This study aims to explore student views on the use of VR in learning anatomy and physiology, and to examine the influence of factors such as perceived usefulness, ease of use, motivation, engagement, satisfaction, and perceived learning outcomes on students’ intention to use VR. Adopting a quantitative approach through a survey method, data were collected from 114 biomedical students in Malaysia and Indonesia via online questionnaire. The data were analyzed using Structural Equation Modeling. The results reveal that motivation, engagement, perceived usefulness, satisfaction, and perceived learning outcomes significantly influence the intention to use VR. Satisfaction also plays a key mediating role between perceived usefulness and intention to use. Meanwhile, ease of use does not exert a direct influence on intention, but shows an indirect effect through perceived usefulness. These findings underscore that students prioritize pedagogical value and enjoyable learning experiences over purely technical aspects. In conclusion, VR is not merely a supplementary tool but serves as a catalyst in accelerating the transformation of biomedical education toward approaches that are more adaptive to the needs of the modern generation. This study contributes by providing empirical evidence to support the development of effective and sustainable technology-based learning tools.